The fugitive - Tagore, Rabindranath, 1861-1941 (Salt Lake City, UT : Project Gutenberg, 2005)
"The Fugitive" by Rabindranath Tagore is a collection of lyrical poems written during the late 19th century. This work delves into themes of love, longing, and existential contemplation, exploring the emotional landscape of characters entwined with the passage of time and nature's beauty. At its heart, the narrative focuses on various characters whose hearts traverse the complexities of relationships, memory, and desire. At the start of the book, the narrator muses about the fleeting nature of existence and the call of the "Eternal Fugitive," reflecting on existence that is characterized by a constant search for meaning and connection. The opening portion encapsulates a poetic dialogue that embodies both personal longing and universal struggle, hinting at relationships formed and lost, as well as the intrinsic beauty of life despite its inherent transience. Through vivid imagery and emotional expression, Tagore introduces readers to a world where the spiritual and temporal intertwine, setting the stage for profound explorations of life and love. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Palataka_(book)
Release date is 2005-04-01
Produced by Eric Eldred, Christine De Ryck, Charles Franks, and the Online Distributed Proofreading Team
Keywords: Indic poetry -- Translations into English